COMPARATIVE ANALYSIS OF IMMEDIATE RESULTS OF PROSTHETIC PLASTY IN EXTENSIVE AND GIANT INCISIONAL VENTRAL HERNIAS - Xujabaev Safarboy Tuxtabayevich,; Dusiyarov Muxammad Mukumboevich; Sherkulov Kodir Usmonkulovich (Scholar Express Journals, 2023)
The article raises the pressing issue of operative therapy for extensive and giant incisional ventral hernias. The authors provided a comparative analysis of various methods of ventral hernia plasty, including the use of a modified method of giant hernia plasty. Incidence of wound complications development was thoroughly noted after each type of plasty. Collective results of the uncomplicated course of the post operative period in the comparison groups were analyzed.
Keywords: Ventral hernias; thoroughly; operative; incisional